THE "BEGEPEN" TRADITION AS A SYMBOL OF PEACE AND UNIVERSITY IN THE EFFORT OF STRENGTHENING THE NATION'S SELF IN THE TRADITIONAL SERVICES OF THE ODUNG BAORAJA TRIBE (Lectio: Journal of Language and Language Teaching, 2025)
The ritual of the peaceful banquet is one of the growing and still robust traditions, maintained inalmost all areas in Lembata. In the east of Atadei, the ritual of a peaceful banquet known as'begepen'. Odung is one of the clans in Atadei that is still maintaining the begepen ritual. Begepenis held in every ritual that involves all members of the clan. Begepen is a central ritual for familymembers when entering the clan's house (una rayan). The ritual is held to gather all familymembers and their forefathers. Begepen is a family's peaceful banquet based on a lovely sense andstrong presence among the family members. In addition, this concept contains values described assimilarity, brotherhood, openness and forgiveness. Begepen is a forefather heir tradition thatimproves each mistake, unites, and tightens the brotherhood among the clan members with theirforefather. A form of brotherhood is once again an attempt to strengthen the identity of membersof the Odung clan, particularly Indonesians. It indicates that the people in Atadei are still verystrong in maintaining and performing the tradition that offers the values of courtesy as a nationalglorious culture.
Keywords: Begepen; national identity; peace; Odung tribe